Android-Based Learning Media Using MIT App Inventor on Algebra Materials for Junior High School Student - Amri, Arif Rahman; Anggraini, Villia; Fitri, Dewi Yuliana (Pelangi (e-Journal), 2023)
During the Covid-19 pandemic, the learning system in Indonesia was carried out online. In the context of learning mathematics for junior high school students, especially algebra material, this online learning system makes students confused and do not focus on the learning material. As a result, students are unable to answer or complete or solve the algebra problems given. This situation then has a big impact on learning outcomes. For that reason, this research propose Android-Based Learning Media using MIT App Inventor on Algebra Materials. This research designed as part of development which conducted the assessment phase. Based on data analysis, it can be concluded that Android-Based Learning Media using MIT App Inventor on Algebra Materials obtained a value of 89.67% with the valid category from the expert, practicality test results scored 82.44% students with very practical categories. As the conclusion the android-based MIT App Inventor learning media on algebra material is appropriate for use in the learning process.